An analytical study of the locations of the new cities in Iraq: Location of Al-Mutanabbi city Model - Mohammed, Amna; Alrikabi, Nada (Al-Adab Journal, 2025)
Iraq does not differ much in its urban problems from the rest of the third and developed world countries in terms of the need for service lands, which is constantly increasing, which has led to illegal encroachment on legal land uses, distorting the aesthetics and environment of cities and affecting the level of quality of life in them. For the purpose of choosing the best solutions to overcome them and to increase the efficiency of development projects and the sustainability of urban life, and as the reality of the situation in Iraqi cities shows, the ideal solution is to think about the policy of establishing new cities, and to attract and completely contain the mother cities of additional cities, that is, real cities that are independent economically, physically and physically (not satellite cities). ) It can share the burdens of urbanization with the mother city, to reach a wide network of cities and effectively connect them with extraordinary paths, seeking to achieve a kind of functional integration and mutual services among them, and to meet the housing need of the mother city. the research problem stemmed from the haziness and lack of clarity of the useful foundations and indicators for selecting new city locations (the inadequacies in locating the new city in accordance with the planning vision and regional relations) and the reliance on land availability alone, , according to a hypothesis that implementing the foundations and principles for selecting new city locations contributes to growth’s success and continuity. The research aims to identify indicators that can be used to select appropriate locations for the planning and implementation of new cities through sustainable integration applications. Al-Mutanabbi, a recently established city, was used as an applied example in the study and analysis of new city planning. The research dealt with two main axes: the first dealt with the policy of the new city, its objectives, classification and positioning, and the second presented the concept of sustainable integration and its practical applications between cities and adopted the method of the analytical approach for the location of the new city of Al-Mutanabbi in Wasit Governorate, to reach the most important indicators of achieving spatial suitability in the signing of new Iraqi cities. Reaching approved standards in the future when signing new cities.